Metabolomic and Transcriptomic Analyses Reveal the Factors Underlying Mature Fruit Pericarp Color Variations in the ‘Xinli No. 7’ Pear (Pyrus sinkiangensis) - Yi Wang; Can Lu; Pan Yan; Shijie An; Ling Ma; Qiangqing Zheng; Yonghui Deng; Qiling Chen (Metabolites)
Background/Objectives: The ‘Xinli No. 7’ pear is a new pear variety with the advantages of early ripening, high quality, high storage resistance, and a long shelf life. Peel color is an important appearance-related trait and an important indicator of fruit quality and commercial value. Methods: In this study, we investigated the polyphenol compound biosynthesis metabolic pathway in the fruit pericarp of ‘Xinli No. 7’ pear using metabolomic and transcriptomic approaches, and qRT–PCR was used for the relative expression analysis of 21 DEGs associated with flavonoid biosynthesis. Results: A total of 128 phenolic compounds were identified, along with 1850 differently expressed genes (DEGs) in peels of different colors. Caftaric acid, apigenin, astragalin, phlorizin, prunin, taxifolin, rutin, naringenin, and their derivatives were abundant in the peel of ‘Xinli No. 7’ pear. An integrated analysis of transcriptomic and metabolomic data revealed that one PGT1, one LAR, two ANS, three 4CL, one CHS, one DFR, and one CHI gene involved in flavonoid biosynthesis exhibited markedly different expression levels in the fruit pericarp of ‘Xinli No. 7’ pear. Metabolic profiling of pear skin led to the identification of polyphenol substances involved in the flavonoid biosynthetic process and revealed 16 flavonoid compounds with high accumulation in pear fruit with red skin (PR). Notably, MYBs (25), bHLHs (18), WRKYs (15), NACs (15), ERFs (15), and MADs (2) may also contribute to the accumulation of flavonoid metabolites and the biosynthesis of anthocyanins in the peel of ‘Xinli No. 7’. Conclusions: Therefore, our results demonstrate the key role of phenolic compounds and candidate transcription factors involved in the peel color formation of ‘Xinli No. 7’ pear fruit.